The Methodological Position of Symbolic Interactionism - Blumer, Herbert (Sociologija. Mintis ir veiksmas, 1998)
Translation: Blumer, Herbert. 1969. Symbolic Interactionism. Perspective and Method, Englewood Cliffs: Prentice-Hall; 1-21.